2014
DOI: 10.1136/bmjqs-2013-002364
|View full text |Cite
|
Sign up to set email alerts
|

Improving transition from paediatric to adult cystic fibrosis care: programme implementation and evaluation

Abstract: Background The paradigm of cystic fibrosis (CF) care has changed as effective therapies extend the lives of patients well into adulthood. Preparing for and maintaining high quality CF care into the adult healthcare setting is critical for prolonged survival. Unfortunately, this transfer process from the paediatric to the adult CF centre is met with a variety of challenges. Objective and methods The objective of this quality improvement (QI) project was to develop, implement and evaluate a theory-based progra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
49
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(52 citation statements)
references
References 28 publications
(11 reference statements)
1
49
0
1
Order By: Relevance
“…Examples of comprehensive programs include The Netherlands' national program for transitional care for young people with chronic conditions, ''On Your Own Feet Ahead'' [89,90], and the University of California San Francisco's cystic fibrosis transition program [91]. The latter is a particularly good example of collaborative efforts between pediatric and adult care providers to improve and standardize the transition process resulting in a durable pediatric-adult collaboration and harmonization of care; early evaluation of this pilot project showed a trend toward improved patient readiness for transfer and decreased hospitalization post transfer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Examples of comprehensive programs include The Netherlands' national program for transitional care for young people with chronic conditions, ''On Your Own Feet Ahead'' [89,90], and the University of California San Francisco's cystic fibrosis transition program [91]. The latter is a particularly good example of collaborative efforts between pediatric and adult care providers to improve and standardize the transition process resulting in a durable pediatric-adult collaboration and harmonization of care; early evaluation of this pilot project showed a trend toward improved patient readiness for transfer and decreased hospitalization post transfer.…”
Section: Discussionmentioning
confidence: 99%
“…The latter is a particularly good example of collaborative efforts between pediatric and adult care providers to improve and standardize the transition process resulting in a durable pediatric-adult collaboration and harmonization of care; early evaluation of this pilot project showed a trend toward improved patient readiness for transfer and decreased hospitalization post transfer. A useful mechanism by which to develop a transition program is as a quality improvement initiative [91][92][93][94].…”
Section: Discussionmentioning
confidence: 99%
“…There is universal consensus in viewing transition as a process on a continuum, rather than as an isolated, one-time event (AAP, 2013;Anie & Telfair, 2005;Blum et al, 2002;Higgins & Tong, 2003;Hobbie & Ogle, 2001;Kelly et al, 2002;Lewis-Gary, 2001;Okumura et al, 2014;Oskoui, 2012;Pinzon et al, 2004;Reiss & Gibson, 2002;Rosen, 2004;Sawin et al, 1999;Scal, 2002;Soanes & Timmons, 2004;Swallow et al, 2013;Telfair et al, 2004aTelfair et al, , 2004bTowns & Bell, 2010).…”
Section: Contextual Basis Attributesmentioning
confidence: 96%
“…This was identified in six sources (Bates et al, 2003;Callahan et al, 2001;Davis et al, 2014;Luppino et al, 2003;Okumura et al, 2014;Oskoui, 2012;Towns & Bell, 2010). The authors attempted to deliver a caveat that transition is not to be equated with transfer of care.…”
Section: Surrogate Termsmentioning
confidence: 97%
“…A handful of studies have demonstrated a positive effect of disease-specific transition programs on patient or healthcare system outcomes 16,17,18 .…”
mentioning
confidence: 99%